Geología de los cuadrángulos de Lagunas, Río Cauchío, Santa Cruz, Río Sacarita, Río Samiria, Bretaña, Requena, Remoyacu, Angamos, Santa Isabel, Tamanco, Nueva Esperanza, Buenas Lomas, Laguna Portugal, Puerto Rico, Tabalosos, Curinga, Quebrada Capanahua, Quebrada Betilia y Río Yaquerana 11-l, 11-m, 11-n, 11-ñ, 11-o, 11-p, 11-q, 12-l, 12-m, 12-n, 12-ñ, 12-o, 12-p, 12-q, 13-ñ, 13-o, 13,p, 14-ñ, 14-o, 14-p – [Boletín A 134] - De la Cruz Bustamante, Natalio Senen (1999)
255 p. 20 mapas